Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan Pegawai Kantor Pusat Pelatihan Sumber Daya Manusia Ekspor dan Jasa Perdagangan Jakarta - Fadillah, Anissa; Purwatiningsih, Purwatiningsih (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The performance of a company is highly influenced by its employees. Therefore, human resources deserve substantial attention from management, particularly regarding employee discipline, work quality, and the potential to improve work discipline. This study employed a quantitative descriptive method with a sample of 95 respondents. Data were collected through observation, interviews, questionnaires, and documentation. The findings reveal a significant partial effect between work discipline and employee performance, as demonstrated by the results of the t-test (probability value 0.000; t-value 3.369 > t-table 1.66159). Furthermore, there is a significant partial influence between work motivation and employee performance, as evidenced by the t-test results (probability value 0.000; t-value 4.251 > t-table 1.66159). In addition, a significant simultaneous effect of work motivation and work discipline on employee performance was identified at the Head Office of Export and Trade Services Human Resources Training. This was confirmed by the F-test results (probability value 0.000; F-value 9.598 > F-table 2.70). These results indicate that both work discipline and work motivation play a critical role in shaping employee performance. Strengthening employee discipline and motivation can therefore enhance organizational effectiveness and lead to improved performance outcomes. This study underscores the importance of human resource management practices focused on discipline and motivation as key drivers of organizational success and sustainable performance improvements in service-oriented institutions.